Transitions without justice: Bhutanese refugees in Nepal - Neikirk, Alice (International journal of transitional justice, 2024)
Typically, human rights abusers are widely condemned by the international community in the context of transitional justice. But what happens when the transition to democracy generates refugees that are not permitted to return to what appears to now be a stable, peaceful democracy? This is the case of Bhutan, who forcefully expelled its largest minority community during a period of nation building, then successfully transitioned to democracy without any accountability for the crimes that occurred during that process. While approximately 100,000 Bhutanese refugees in camps awaited some measure of justice and hoped for repatriation, the international community provided them with a democratically grounded education to raise awareness of their rights. But this education was not matched by any pathways to exercise those rights or achieve justice. This article examines how particular challenges to transitional justice are experienced by refugee and diaspora communities, and how current justice structures frequently fail to meet their needs.